Pengaruh Green Marketing, Life Style, Dan Kesadaran LingkunganTerhadap Keputusan Pembelian Konsumen (Studi Kasus Pada Konsumen Damar Coffee Kota Malang) - Abdul Kodir; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the simultaneous influence of green marketing, life style and environmental awareness variables on consumer purchasing decisions at Damar Coffee. Damar Coffee customers served as the subject of this study. Quantitative research is the focus of this study. In this case study, questionnaires were distributed to Damar Coffee customers chosen through a straightforward random sampling method to collect data. Using the results of 80 respondents and the Maholtra formula, determining the number of samples. Data were analyzed using multiple linear regression tests and determination tests. Based on the results of data analysis, the results of the F test show that simultaneously green marketing, life style and environmental awareness have a significant effect on consumer purchasing decisions at Damar Coffee. Furthermore, the results of the t test show that green marketing and environmental awareness have a positive and significant effect on consumer purchasing decisions at Damar Coffee. Meanwhile, the lifestyle variable does not have a significant influence on consumer purchasing decisions at Damar Coffee. The results of the determination test show a proportion of 60.2%, where purchasing decisions can be influenced by green marketing, lifestyle and environmental awareness. Based on the limitations in this study, it is hoped that future researchers will use the data collection method using an e-questionnaire (online questionnaire). Using an online questionnaire is expected to be aligned with further research reviews related to green marketing and reducing paper waste. Keywords: Purchase Decision, Green Marketing, Life Style, Environmental Awareness.